Building questions along the way. Native and scientific communities - Guichón, Ricardo A. (Revista del Museo de Antropología, 2016)
Aside from the experiences and attitudes that each individual might have towards the relationship between indigenous communities and researchers, we present the need to rethink the “scenarios” where we are interact. Our analysis will be guided by the dialogue between personal experiences and ideas brought by specific authors outside the archaeological literature. This is an analysis, where Lederach´s perspective on the “complex social conflicts” is explored; the” community mediation” of Nato and coauthors is introduced and finally Morín, Capra, Garcia and Najmanovich gave their perspectives on “complexity”. Our journey begins with what we call linear model of the relationship between indigenous (CO) and scientific (CI) communities. The next step takes us to the “prosecution” and other ways of dealing with conflicts. Then we advance through the different attitudes towards the conflict. Here we enter into a nonlinear model of the relationship between CO and CI. This journey to get to something called “Building spaces for dialogue”.